Comprehensive Study of Climate Change, Occupational Health, and Policy Strategies in Public Healthcare - Alhareth, Mohammed Nasser Ali; AL-Alhareth, Hamad Nasser Ali; Al salem, Nasser Hamad Nasser; Alsalem, Mohammed Hamad Naser; Alyami, Mohammed Mana Saleh; Alaljafer, Ali Mahdi Doman; Al Qalyan, Meshari Hamad Hussain; Al murayh, Ali Mohammed Saleh; Alzmanan, Ahmed Mahdi Ali (Journal of Ecohumanism, 2024)
Global warming is a global threat to human health, primarily in the area of the working population’s occupational health and the sustainability of healthcare delivery systems. Heat stress and respiratory and infectious diseases elaborate employee risks as summer temperatures increase; weather becomes extreme, and air quality declines across occupational segments ranging from agriculture to healthcare. Many of these changes also affect public health care infrastructure very greatly, which in turn faces significant challenges in attempting to mitigate multiple-fold impacts of climate change. In an overview of these works and data, this research explores how climate change affects occupational health and public health policy in general and for the working population in particular. It looks for the major deficiencies in the current strategies and the support system necessary to safeguard workers in vulnerable climate zones. In addition, the study makes use of integrated policy approaches with a focus on climate adaptation in occupational health policies. The study indicates several gaps that should be addressed in the existing system to increase its robustness, strengthen workforce capability, and build climate-resilient facilities and infrastructure. These reforms seek to lessen the impacts of climate change on workers’ health by increasing the healthcare system’s ability to address new climate-related diseases